Small and medium entrepreneurship in Russia: Luxembourg, 7 November 2013 - European Investment Bank (European Investment Bank (EIB), 2014)
This study was prepared for the European Investment Bank (EIB). The objective of the study is to assess the financing needs of SMEs in Russia and identify the market failures. In addition to senior debt, which is the main instrument currently available to the EIB in Russia, the study also examines the needs for risk-bearing instruments as well as SME loan guarantees and other financial instruments, and the contribution of capital markets.
Keywords: 330